Senhoras de si : problematizando as incidências das biopolíticas nos corpos que sangram e co-produzindo narrativas que (re)inventam a vida a partir da prática do aborto - Barone, María Antonella (2018)
The present writing is the result of a research route made by the Ladies of Si, which is added to the efforts of those who precede them. They are the narratives of the pregnant bodies that abort and that collectivize the affections of their experiences with information, reports, stories on the Internet and beyond. Also, we co-created with them short stories to tell stories of life and abortion. Thinking about the context of criminalization of abortion in Brazil, we problematize the effects of biopolitics on the bodies that bleed and abort, and we are willing, in this research, to produce with them other images about abortive practice. We put ourselves in the task of co-producing alternate images, life-images through paintings, poetry, songs, comics, comics, illustrations, cinema, documentaries, performances and other artistic works that have the political potential to produce other narratives about the practice of abortion. In this way, we highlight the concept of artivism (neologism composed by the words art and activism) as a possibility that calls into question the idea of abortion as trauma, taking away the myths and the drama that is produced about it. The art tool allows us to create other infamous and inventive narratives as a form of activism that, together with feminisms and in dialogues with other knowledge, produce networks and trigger collective rhizomes, thus producing a common. We do not do in this work, an examination of what would define a definition of art, what interests us are the assemblages that the interpenetration of both concepts - art and activism - produce. The text contains some reflections on the possibility of thinking about the production of abortive subjectivities, which are those that intervene in the processes and propose alternative meanings on the practice of abortion. In the creation of networks of solidarity, the abortionists are put into action. In these practices they produce other possible ones, thus questioning the norms and their structures. We bring in the text, a problematization of intersectionality as a category of analysis that presents possibilities and some limits. We also ask ourselves about the interference of laws in the bodies that abort and the possibility of legitimizing the practice that we consider necessary to analyze when making policies for a social transformation. Because we care about life, this text (re) exists. We place special emphasis on the importance of reclaiming the concept of life to talk about abortion. So we ask ourselves what life matters to us?